Process optimization and in vivo performance of docetaxel loaded PHBV-TPGS therapeutic vesicles: A synergistic approach - Vardhan H.; Mittal P.; Adena S.K.R.; Upadhyay M.; Yadav S.K.; Mishra B. (My University, 2025)
This research was motivated due to substantial requirement of improved treatment for breast cancer which accounts for over 0.52 million deaths annually worldwide. Utilizing nanoparticles carrying active medicaments as targeted delivery carrier is emerging as a promising approach. For a drug to be clinically effective, it needs to be suitably protected in the biological fluid till it is delivered to the targeted site. Keeping above in mind, we prepared and optimized polymeric nanoparticles by polyhydroxybutyrate-co-hydroxyvalerate (PHBV) a biodegradable polymer utilizing modified emulsification solvent evaporation method. The optimized formulation had particle size of 349 ± 3.51 nm with entrapment efficiency of 69 ± 1.28%. Nanoparticle formation and its surface morphology were confirmed by various electron microscopes. The in vitro and pharmacokinetic studies demonstrated a sustained release of drug in a non-biological system and into rat's bloodstream respectively. Also, the in vitro cytotoxicity and in vivo toxicological evaluation at the therapeutic dose demonstrated the safety and antitumor efficacy of the formulation. Due to formulation characteristic properties, it was found to be effective in enveloping and chaperoning the drug to the suitable site of action. The PHBV-TPGS combination causes the drug to be released in controlled and sustained modes, thereby reducing drug dose and toxicity. © 2017 Elsevier B.V.